Digital Turn in Malaysian Quantity Surveying Practices: Big Data Analytics Pathway for Forward Thinking Professionals - Zafira Nadia Maaz,; Norhazren Izatie Mohd,; Amalina Azmi, (2026)
This book is written for Quantity Surveyors who recognise the need to evolve from conventional cost and measurement roles towards data driven strategic roles, yet remain unsure how to begin within the Malaysian construction landscape. Digital Turn in Malaysian Quantity Surveying Practices presents an in-depth exploration of how Big Data Analytics is redefining professional roles, competencies, and value. Blending local policy, industry practice, and case-based insight, it guides readers from cost analytics to digital data governance, empowering Quantity Surveyors as strategic decision makers.